# 4.1 Properties of the laplace transform

 Page 1 / 2
Derives basic properties of the Laplace transform.

## Properties of the laplace transform

The properties associated with the Laplace transform are similar to those of the Fourier transform. First, let's set define some notation, we will use the notation $\mathfrak{L}\left\{\right\}$ to denote the Laplace transform operation. Therefore we can write $X\left(s\right)=\mathfrak{L}\left\{x,\left(,t,\right)\right\}$ and $x\left(t\right)={\mathfrak{L}}^{-1}\left\{X,\left(,s,\right)\right\}$ for the forward and inverse Laplace transforms, respectively. We can also use the transform pair notation used earlier:

$x\left(t\right)↔X\left(s\right)$

With this notation defined, lets now look at some properties.

## Linearity

Given that ${x}_{1}\left(t\right)↔{X}_{1}\left(s\right)$ and ${x}_{2}\left(t\right)↔{X}_{2}\left(s\right)$ then for any constants $\alpha$ and $\beta$ , we have

$\alpha {x}_{1}\left(t\right)+\beta {x}_{2}\left(t\right)↔\alpha {X}_{1}\left(s\right)+\beta {X}_{2}\left(s\right)$

The linearity property follows easily using the definition of the Laplace transform.

## Time delay

The reason we call this the time delay property rather than the time shift property is that the time shift must be positive, i.e. if $\tau >0$ , then $x\left(t-\tau \right)$ corresponds to a delay. If $\tau <0$ then we would not be able to use the single-sided Laplace transform because we would have a lower integration limit of $\tau$ , which is less than zero. To derive the property, lets evaluate the Laplace transform of the time-delayed signal

$\mathfrak{L}\left\{x,\left(,t,-,\tau ,\right)\right\}={\int }_{0}^{\infty }x\left(t-\tau \right){e}^{-st}dt$

Letting $\gamma =t-\tau$ leads to $t=\gamma +\tau$ and $dt=d\gamma$ . Substituting these quantities into [link] gives

$\begin{array}{ccc}\hfill \mathfrak{L}\left\{x,\left(,t,-,\tau ,\right)\right\}& =& {\int }_{-\tau }^{\infty }x\left(\gamma \right){e}^{-s\left(\gamma +\tau \right)}d\gamma \hfill \\ & =& {e}^{-s\tau }{\int }_{-\tau }^{\infty }x\left(\gamma \right){e}^{-s\gamma }d\gamma \hfill \\ & =& {e}^{-s\tau }{\int }_{-\tau }^{0}x\left(\gamma \right){e}^{-s\gamma }d\gamma +{e}^{-s\tau }{\int }_{0}^{\infty }x\left(\gamma \right){e}^{-s\gamma }d\gamma \hfill \end{array}$

where we note that the first integral in the last line is zero since $x\left(t\right)=0,t<0$ . Therefore the time delay property is given by

$\mathfrak{L}\left\{x,\left(,t,-,\tau ,\right)\right\}={e}^{-s\tau }X\left(s\right)$

## S-shift

This property is the Laplace transform corresponds to the frequency shift property of the Fourier transform. In fact, the derivation of the $s$ -shift property is virtually identical to that of the frequency shift property.

$\begin{array}{ccc}\hfill \mathfrak{L}\left\{{e}^{-at},x,\left(t\right)\right\}& =& {\int }_{0}^{\infty }{e}^{-at}x\left(t\right){e}^{-st}dt\hfill \\ & =& {\int }_{0}^{\infty }x\left(t\right){e}^{-\left(a+s\right)t}dt\hfill \\ & =& {\int }_{0}^{\infty }x\left(t\right){e}^{-\left(a+\sigma +j\Omega \right)t}dt\hfill \\ & =& X\left(s+a\right)\hfill \end{array}$

The $s$ -shift property also alters the region of convergence of the Laplace transform. If the region of convergence for $X\left(s\right)$ is $\sigma >{\sigma }_{min}$ , then the region of convergence for $\mathfrak{L}\left\{{e}^{-at},x,\left(t\right)\right\}$ is $\sigma >{\sigma }_{min}-\text{Re}\left(a\right)$ .

## Multiplication by $t$

Let's begin by taking the derivative of the Laplace transform:

$\begin{array}{ccc}\hfill \frac{dX\left(s\right)}{ds}& =& \frac{d}{ds}{\int }_{0}^{\infty }x\left(t\right){e}^{-st}dt\hfill \\ \hfill & =& {\int }_{0}^{\infty }x\left(t\right)\frac{d}{ds}{e}^{-st}dt\hfill \\ \hfill & =& -{\int }_{0}^{\infty }tx\left(t\right){e}^{-st}dt\hfill \end{array}$

So we can write

$\mathfrak{L}\left\{t,x,\left(,t,\right)\right\}=-\frac{dX\left(s\right)}{ds}$

This idea can be extended to multiplication by ${t}^{n}$ . Letting $y\left(t\right)=tx\left(t\right)$ , if follows that

$\begin{array}{ccc}\hfill ty\left(t\right)& ↔& -\frac{dY\left(s\right)}{ds}\hfill \\ \hfill & ↔& \frac{{d}^{2}X\left(s\right)}{d{s}^{2}}\hfill \end{array}$

Proceeding in this manner, we find that

${t}^{n}x\left(t\right)↔{\left(-1\right)}^{n}\frac{{d}^{n}X\left(s\right)}{d{s}^{n}}$

## Time scaling

The time scaling property for the Laplace transform is similar to that of the Fourier transform:

$\begin{array}{ccc}\hfill \mathfrak{L}\left\{x,\left(,\alpha ,t,\right)\right\}& =& {\int }_{0}^{\infty }x\left(\alpha t\right){e}^{-st}dt\hfill \\ \hfill & =& \frac{1}{\alpha }{\int }_{0}^{\infty }x\left(\gamma \right){e}^{-\frac{s}{\alpha }\gamma }d\gamma \hfill \\ \hfill & =& \frac{1}{\alpha }X\left(\frac{s}{\alpha }\right)\hfill \end{array}$

where in the second equality, we made the substitution $t=\frac{\gamma }{\alpha }$ and $dt=\frac{d\gamma }{\alpha }$ .

## Convolution

The derivation of the convolution property for the Laplace transform is virtually identical to that of the Fourier transform. We begin with

$\begin{array}{ccc}\hfill \mathfrak{L}\left\{{\int }_{-\infty }^{\infty },x,\left(\tau \right),h,\left(t-\tau \right),d,\tau \right\}& =& {\int }_{-\infty }^{\infty }x\left(\tau \right)\mathfrak{L}\left\{h,\left(,t,-,\tau ,\right)\right\}d\tau \hfill \end{array}$

Applying the time-delay property of the Laplace transform gives

$\begin{array}{ccc}\hfill {\int }_{-\infty }^{\infty }x\left(\tau \right)\mathfrak{L}\left\{h,\left(,t,-,\tau ,\right)\right\}d\tau & =& H\left(s\right){\int }_{-\infty }^{\infty }x\left(\tau \right){e}^{-s\tau }d\tau \hfill \\ & =& H\left(s\right)X\left(s\right)\hfill \end{array}$

If $h\left(t\right)$ is the the impulse response of a linear time-invariant system, then we call $H\left(s\right)$ the system function of the system. The frequency response results by setting $s=j\Omega$ in $H\left(s\right)$ . The system function provides us with a very powerful means of determining the output of a linear time-invariant filter given the input signal. It will also enable us to determine a means of establishing the stability We will discuss stability shortly of a linear-time invariant filter, something which was not possible with the frequency response.

explain and give four Example hyperbolic function
The denominator of a certain fraction is 9 more than the numerator. If 6 is added to both terms of the fraction, the value of the fraction becomes 2/3. Find the original fraction. 2. The sum of the least and greatest of 3 consecutive integers is 60. What are the valu
1. x + 6 2 -------------- = _ x + 9 + 6 3 x + 6 3 ----------- x -- (cross multiply) x + 15 2 3(x + 6) = 2(x + 15) 3x + 18 = 2x + 30 (-2x from both) x + 18 = 30 (-18 from both) x = 12 Test: 12 + 6 18 2 -------------- = --- = --- 12 + 9 + 6 27 3
Pawel
2. (x) + (x + 2) = 60 2x + 2 = 60 2x = 58 x = 29 29, 30, & 31
Pawel
Mark and Don are planning to sell each of their marble collections at a garage sale. If Don has 1 more than 3 times the number of marbles Mark has, how many does each boy have to sell if the total number of marbles is 113?
Mark = x,. Don = 3x + 1 x + 3x + 1 = 113 4x = 112, x = 28 Mark = 28, Don = 85, 28 + 85 = 113
Pawel
how do I set up the problem?
what is a solution set?
Harshika
find the subring of gaussian integers?
Rofiqul
hello, I am happy to help!
Abdullahi
hi mam
Mark
find the value of 2x=32
divide by 2 on each side of the equal sign to solve for x
corri
X=16
Michael
Want to review on complex number 1.What are complex number 2.How to solve complex number problems.
Beyan
yes i wantt to review
Mark
use the y -intercept and slope to sketch the graph of the equation y=6x
how do we prove the quadratic formular
Darius
hello, if you have a question about Algebra 2. I may be able to help. I am an Algebra 2 Teacher
thank you help me with how to prove the quadratic equation
Seidu
may God blessed u for that. Please I want u to help me in sets.
Opoku
what is math number
4
Trista
x-2y+3z=-3 2x-y+z=7 -x+3y-z=6
can you teacch how to solve that🙏
Mark
Solve for the first variable in one of the equations, then substitute the result into the other equation. Point For: (6111,4111,−411)(6111,4111,-411) Equation Form: x=6111,y=4111,z=−411x=6111,y=4111,z=-411
Brenna
(61/11,41/11,−4/11)
Brenna
x=61/11 y=41/11 z=−4/11 x=61/11 y=41/11 z=-4/11
Brenna
Need help solving this problem (2/7)^-2
x+2y-z=7
Sidiki
what is the coefficient of -4×
-1
Shedrak
the operation * is x * y =x + y/ 1+(x × y) show if the operation is commutative if x × y is not equal to -1
A soccer field is a rectangle 130 meters wide and 110 meters long. The coach asks players to run from one corner to the other corner diagonally across. What is that distance, to the nearest tenths place.
Jeannette has $5 and$10 bills in her wallet. The number of fives is three more than six times the number of tens. Let t represent the number of tens. Write an expression for the number of fives.
What is the expressiin for seven less than four times the number of nickels
How do i figure this problem out.
how do you translate this in Algebraic Expressions
why surface tension is zero at critical temperature
Shanjida
I think if critical temperature denote high temperature then a liquid stats boils that time the water stats to evaporate so some moles of h2o to up and due to high temp the bonding break they have low density so it can be a reason
s.
Need to simplify the expresin. 3/7 (x+y)-1/7 (x-1)=
. After 3 months on a diet, Lisa had lost 12% of her original weight. She lost 21 pounds. What was Lisa's original weight?
Got questions? Join the online conversation and get instant answers! By Brooke Delaney By OpenStax By Tess Armstrong By Angela Eckman By JavaChamp Team By Richley Crapo By Madison Christian By Katy Keilers By Inderjeet Brar By OpenStax